Informing the Uninformed, Sensitizing the Informed: The Two Sides of Consumer Environmental Awareness - Dorothée Brécard; Mireille Chiroleu-Assouline (CESifo GmbH, 2025)
How do environmental information and awareness interact to improve environmental quality by changing consumer behavior and firm strategies? This article provides theoretical insights using an original differentiation model within a general framework whose specific cases have been studied previously. On the demand side, only informed consumers differentiate brown from green product quality, while uninformed consumers consider these perfect substitutes. Moreover, all informed consumers value the green product and devalue the brown product as a result of an aversion effect but are heterogeneous in their environmental awareness. On the supply side, two firms offer different environmental qualities and compete on price. We consider two types of environmental campaigns: one that increases the number of informed consumers and one that increases the environmental awareness of informed consumers. We show that these campaigns crucially determine three market configurations: segmented; fragmented, with a brown product that appeals to both uninformed consumers and a fraction of informed consumers; and covered. Assuming that the greenest consumer behavior is abstention, we find that both campaigns do not always lead to better environmental quality; that is, a situation in which all consumers are informed and some highly environmentally aware is not necessarily the greenest situation. Depending on the aversion effect, the budget of the campaign organizer, and their relative cost-effectiveness, information and awareness-raising campaigns must be carefully combined to achieve the best possible environmental quality.
Keywords: D11; D62; D83; L15; Q58; 330; information campaign; NGO campaign; environmental awareness; environmental quality; vertical product differentiation